2015
DOI: 10.1016/j.clinph.2014.10.140
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dorsal premotor–motor inhibition in cervical dystonia

Abstract: Objective This study aims to understand whether the enhanced dPMI, seen in writer’s cramp patients previously, extends to other populations of focal dystonia patients (e.g. cervical dystonia) as an endophenotypic marker. Methods We studied 9 healthy subjects and 9 patients with CD. dPMI was tested by applying conditioning transcranial magnetic stimulation to the left dorsal premotor cortex and then a test pulse to the ipsilateral motor cortex at an interval of 6 ms. We also looked at the duration of the cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The CSP evaluation in dystonia has not produced consistent results. Most studies report a decrease (Chen et al, 1997; Filipović et al, 1997; Rona et al, 1998; Pirio Richardson, 2015), or a trend toward a reduction of CSP (Schwenkreis et al, 1999), interpreted as a correlate to the cortical hyperexcitability, more rarely unchanged (Stinear and Byblow, 2004). Furthermore, to assess the neurons membrane excitability in dystonia, the MT, and the RC (Ziemann et al, 1996a; Chen et al, 1997; Werhahn et al, 1999; Ziemann et al, 2004; Murase et al, 2005) were assessed and were consistently normal in both primary and non-primary dystonia (Quartarone et al, 2009; Kojovic et al, 2013).…”
Section: Dystonia and Tms: A Window Into Pathophysiological Insightsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CSP evaluation in dystonia has not produced consistent results. Most studies report a decrease (Chen et al, 1997; Filipović et al, 1997; Rona et al, 1998; Pirio Richardson, 2015), or a trend toward a reduction of CSP (Schwenkreis et al, 1999), interpreted as a correlate to the cortical hyperexcitability, more rarely unchanged (Stinear and Byblow, 2004). Furthermore, to assess the neurons membrane excitability in dystonia, the MT, and the RC (Ziemann et al, 1996a; Chen et al, 1997; Werhahn et al, 1999; Ziemann et al, 2004; Murase et al, 2005) were assessed and were consistently normal in both primary and non-primary dystonia (Quartarone et al, 2009; Kojovic et al, 2013).…”
Section: Dystonia and Tms: A Window Into Pathophysiological Insightsmentioning
confidence: 99%
“…A conditioning TMS was applied to the dorsal PMC and then a test pulse to the ipsilateral motor cortex, at an interval of 6 ms, in nine patients with cervical dystonia, compared to nine healthy subjects. It resulted in enhanced dorsal premotor–motor cortical inhibition, independent of the severity of the disease (Pirio Richardson, 2015). This enhanced inhibition is more consistent with an endophenotypic marker widespread in the brain, as it has been evidenced in the setting of task-specific dystonia, such as writer’s cramp (Pirio Richardson et al, 2014), and is hypothesized by the authors as compensatory to reduce abnormal motor output and sustained muscle contraction.…”
Section: Dystonia and Tms: A Window Into Pathophysiological Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical dystonia is a chronic neurological disorder characterized by sustained and involuntary contractions of the neck muscles, and is the most common form of focal dystonia (Xiao et al, 2012). Cervical dystonia has traditionally been ascribed to dysfunction of the basal ganglia (Galardi et al, 1996;Naumann et al, 1998), but abnormalities have been observed in many other brain regions including the cerebellum (Batla et al, 2015), prefrontal cortex , midbrain (Holmes et al, 2012), motor cortex (Richardson, 2015), and somatosensory cortex (Prudente et al, 2016). This has led to the suggestion that cervical dystonia is a 'network disorder' resulting from dysfunction in multiple different brain regions (Jinnah et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…How these findings may relate to CD in humans remain to be established. Pathological studies and physiological investigations of individuals with CD have pointed to abnormalities of the cerebral cortex, cerebellum, or vestibular pathways (813). Routine clinical imaging studies only rarely reveal overt anatomical defects in the brain in individuals with CD, and these are scattered across many regions such as the cerebral cortex, basal ganglia, cerebellum, midbrain, brainstem, and spinal cord (14).…”
Section: Introductionmentioning
confidence: 99%